2018
DOI: 10.1590/0102-672020180001e1399
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Onlay Laparoscopic Approach (Scola) for Ventral Hernia and Rectus Abdominis Diastasis Repair: Technical Description and Initial Results

Abstract: Background:Diastasis of the rectus abdominis muscles (DMRA) is frequent and may be associated with abdominal wall hernias. For patients with redudant skin, dermolipectomy and plication of the diastasis is the most commonly used procedure. However, there is a significant group of patients who do not require skin resection or do not want large incisions. Aim:To describe a “new” technique (subcutaneous onlay laparoscopic approach - SCOLA) for the correction of ventral hernias combined with the DMRA plication and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(36 citation statements)
references
References 27 publications
0
31
0
5
Order By: Relevance
“…The literature is limited. Six studies were identified: three prospective cohort and three retrospective studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature is limited. Six studies were identified: three prospective cohort and three retrospective studies.…”
Section: Resultsmentioning
confidence: 99%
“…It was concluded that endoscopic repair is feasible, with a low number of wound impairments. One study 35 reported one recurrence of the diastasis, whereas no recurrences of either the umbilical hernia or the rectus diastasis were reported by the others 27,34 .…”
Section: Quality Of Evidence: Strength Of Recommendation: Weakmentioning
confidence: 95%
See 1 more Smart Citation
“…Plication techniques with running sutures and mesh reinforcement are applied most frequently for DRAM repair. Most studies have described the use of mesh reinforcement .…”
mentioning
confidence: 99%
“…Surface electromyography (SEMG), also called kinetic electromyography due to its ability to evaluate muscle activation during movement, is a commonly used instrument in training and rehabilitation analysis of the core muscles and for patients with low back pain 2,14,17 . In a review of the literature, 87 studies involving SEMG and abdominal-wall muscles were found between 1950 and 2008 15 .…”
mentioning
confidence: 99%